Development of a prototype for Johore tourism information system in web environment - Lee, Yen Soo (2002)
Tourism is an information-intensive industry in which its competitiveness today is increasingly determined by the ability to develop and assimilate innovative ways to respond to the dynamic nature of the tourism environment and its new paradigms to provide value-adding tourist services. The study aims to bring about the changes, development and better improvement to the current Johore tourism information system through the effective use of computer technology in terms of information management to provide both value and service to attract more tourists coming to Johore. Based on a use-case driven object-oriented system development methodology, a prototype of Johore Tourism Information System is built. The prototype built incorporates multimedia elements and provide a value-added service to the user based on the characteristic of Decision Support System in which it enable the potential tourist to adjust and access the information according to their own individual needs and can generate a customize trip plan based on the selected destination, budget, departure location and travel priority. The usability test on the prototype shown favourable result though much room for improvement has to be made in order to fully implement the idea proposed in this study.